Organic insulators, metal-clad laminates and wiring boards

By incorporating a specific ratio and distribution of nitrogen-based and phenolic antioxidants in the organic resin phase of the organic insulator, the challenges of maintaining stable dielectric properties at high temperatures are addressed, enhancing the reliability of electronic components.

JP7650962B2Active Publication Date: 2025-03-25KYOCERA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023517609
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-28
Filing Date
2022-04-27
Publication Date
2025-03-25
Estimated Expiration
2042-04-27

AI Technical Summary

Technical Problem

Conventional organic insulators used in electronic components face challenges in maintaining stable dielectric properties at high temperatures, leading to increased relative permittivity and dielectric loss tangent, which can degrade the performance and reliability of electronic equipment.

Method used

The use of an organic insulator composed of an organic resin phase containing a nitrogen-based antioxidant and a phenolic antioxidant, with a specific ratio and distribution of these antioxidants, which helps to prevent oxidation and maintain the glass transition point of the organic resin, thereby stabilizing the dielectric properties even at high temperatures.

Benefits of technology

This solution effectively suppresses the increase in dielectric loss tangent and relative permittivity at high temperatures, ensuring stable dielectric properties and improved reliability of electronic components, even after exposure to high temperatures for extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650962000001
    Figure 0007650962000001
  • Figure 0007650962000002
    Figure 0007650962000002
  • Figure 0007650962000003
    Figure 0007650962000003
Patent Text Reader

Abstract

An organic insulator according to the present disclosure contains an organic resin as the main component thereof, and at least includes in the organic resin: an antioxidant (A) containing a nitrogen atom; and a phenolic antioxidant (B). A metal-clad laminate according to the present disclosure comprises: the organic insulator; and a metal foil laminated on at least one surface of the organic insulator. A wiring board according to the present disclosure comprises: a plurality of insulating layers composed of the organic insulator; and a metal foil disposed between the insulating layers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an organic insulator, and a metal-clad laminate and a wiring board using the same. [Background technology]

[0002] In recent years, the speed and integration of LSIs and the capacity of memories have increased, and accordingly, various electronic components have rapidly become smaller, lighter, and thinner. Conventionally, wiring boards used in the field of such electronic components have used cyclic olefin copolymers as described in Patent Document 1 as insulating materials. Such insulating materials are used, for example, in copper-clad boards with copper foil laminated on their surfaces and wiring boards for high frequency use. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-100843 A Summary of the Invention

[0004] The organic insulator of the present disclosure contains an organic resin phase as a main component, and the organic resin phase contains at least an antioxidant (A) containing a nitrogen atom and a phenol-based antioxidant (B).

[0005] The metal-clad laminate of the present disclosure comprises the above-described organic insulator and a metal foil laminated on at least one surface of the organic insulator.

[0006] The wiring board of the present disclosure includes a plurality of insulating layers made of the above-mentioned organic insulator, and a metal foil disposed between the insulating layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The organic insulator of the present disclosure contains an organic resin as a main component. The organic resin contains an antioxidant (A) containing a nitrogen atom and a phenol-based antioxidant (B). Here, "containing an organic resin as a main component" refers to a case where the proportion of the organic resin contained in the organic insulator is 60 mass% or more.

[0008] Examples of the antioxidant (A) containing a nitrogen atom (hereinafter, sometimes referred to as nitrogen-based antioxidant (A)) include hindered amine compounds. Examples of the phenol-based antioxidant (B) include di-t-butylphenol derivatives. Here, the di-t-butylphenol derivative is preferably a compound containing a di-t-butylhydroxyphenyl group in its structure.

[0009] At high temperatures, the nitrogen-based antioxidant (A) loses its antioxidant effect or undergoes a reaction that causes it to lose its activity. On the other hand, the phenol-based antioxidant (B) containing di-t-butylphenol is capable of reacting even at high temperatures and has the ability to reactivate the deactivated nitrogen-based antioxidant (A). This makes it possible to better prevent oxidation of organic insulators and suppress increases in the dielectric constant and dielectric tangent. On the other hand, the phenol-based antioxidant (B) alone has a high polarity, making it difficult to mix with organic resins and resulting in a weak antioxidant effect. The presence of the nitrogen-based antioxidant (A) and the phenol-based antioxidant (B) makes it easier to mix with organic resins and can exert a stronger antioxidant effect.

[0010] That is, when the organic insulator is left at a high temperature of, for example, 125° C. for a long period of time, the organic resin, which is the main component of the organic insulator, can be prevented from oxidizing. This makes it possible to prevent the dielectric tangent (Df) from increasing, particularly in a high-temperature environment. In addition, since the organic insulator contains the two types of antioxidants (A) and (B), it is possible to prevent the glass transition point (Tg) of the organic resin from decreasing.

[0011] The ratio (A / B) of the nitrogen-based antioxidant (A) to the phenol-based antioxidant (B) is preferably 0.5 or more and 3.1 or less in mass ratio. This allows the dielectric tangent (Df) of the organic insulator to be 0.0045 or less after being left at 125°C for 2000 hours. Preferably, the ratio (A / B) of the nitrogen-based antioxidant (A) to the phenol-based antioxidant (B) is preferably 0.5 or more and 3.0 or less in mass ratio. This allows the dielectric tangent (Df) of the organic insulator to be 0.0038 or less after being left at 125°C for 2000 hours.

[0012] The total amount of the nitrogen-based antioxidant (A) and the phenol-based antioxidant (B) is preferably 0.7 to 4.5 parts by mass per 100 parts by mass of the organic resin, which allows the dielectric loss tangent (Df) of the organic insulator to be kept at 0.0045 or less after being left at 125°C for 2000 hours.

[0013] Preferably, the total amount of the nitrogen-based antioxidant (A) and the phenol-based antioxidant (B) is 0.9 parts by mass or more and 2.1 parts by mass or less per 100 parts by mass of the organic resin, which allows the organic insulator to have a dielectric loss tangent (Df) of 0.0037 or less at 125°C after being left for 2000 hours.

[0014] The contents of the nitrogen-based antioxidant (A) and the phenol-based antioxidant (B) in the organic resin can be measured, for example, by pyrolysis gas chromatography mass spectrometry (GC-MS), which involves burning the organic resin at 600°C in a helium stream and analyzing the components contained in the resin from the generated gas.

[0015] The antioxidants (A) and (B) are preferably contained in a larger amount in the surface region of the organic insulator than in the internal region. When an organic resin is heated in an air atmosphere, the resin bonds with oxygen, and the polarity becomes stronger. On the other hand, if the nitrogen-based antioxidant (A) is present in a larger amount in the surface region of the organic resin than in the internal region, the bonding between the resin and oxygen in the surface region of the organic insulator can be suppressed.

[0016] Here, the surface region of the organic insulator refers to a range including the surface of the organic insulator and extending from the surface to a depth of about 20 μm. On the other hand, the internal region is a portion that is deeper than 20 μm from the surface. In other words, the surface region of the organic insulator preferably has a depth from the main surface that is in a ratio of 0.05 to 0.3 when the thickness of the organic insulator is 1. On the other hand, the internal region of the organic insulator preferably has a thickness ratio in the range of 0.4 to 0.9 when the thickness of the organic insulator is 1.

[0017] The content ratio of the antioxidants (A) and (B) is higher in the surface region than in the internal region means that when the total content ratio of the antioxidants (A) and (B) in the internal region is taken as 1, the total content ratio of the antioxidants (A) and (B) in the surface region is 2 or more. In this case, it is preferable that the total content ratio of the antioxidants (A) and (B) in the surface region is 4 or less.

[0018] The distribution of antioxidants (A) and (B) contained in the organic insulator is determined as follows. First, the surface of the organic insulator is very thinly polished. Next, X-ray photoelectron spectroscopy (XPS) is performed on the newly exposed surface of the organic insulator.

[0019] In this case, the distribution of specific elements detected in the regions other than the organic resin is examined. The content ratio of the antioxidants (A) and (B) is determined, for example, by comparing the element counts indicated by an X-ray spectroscopy (XPS) device between the internal region and the surface region of the organic insulator.

[0020] The content of the antioxidants (A) and (B) in the surface region is determined from the average value of the element counts indicated by an X-ray spectroscopic analysis (XPS) device in the above-mentioned surface region range. On the other hand, the content of the antioxidants (A) and (B) in the internal region is determined from the average value of the counts obtained by performing X-ray spectroscopic analysis (XPS) at 3 to 5 points in the center of the thickness direction of the organic insulator. The part containing a large amount of the antioxidants (A) and (B) is preferably the entire surface of the organic insulator, but it may be provided only in the part where the characteristics need to be maintained. When determining the structural formula of the antioxidants (A) and (B), it is preferable to use a Fourier transform infrared spectroscopic analysis device (FT-IR) and a liquid chromatograph (HPLC). The content of the antioxidants (A) and (B) is compared by the count number of the X-ray spectroscopic analysis (XPS). In this case, a higher count number in the X-ray spectroscopic analysis (XPS) indicates a higher content of the antioxidants (A) and (B), and a lower count number indicates a lower content of the antioxidants (A) and (B).

[0021] In order to ensure that the antioxidants (A) and (B) are contained in a larger amount in the surface region than in the internal region of the organic insulator, for example, when producing a laminate, a sheet-like molded product containing a larger amount of the antioxidant on the surface layer side than on the internal layer side is used.

[0022] In this organic insulator, it is preferable that the antioxidants (A) and (B) are distributed in a layered form. When the portion with a high content of the antioxidants (A) and (B) has a layered form in the surface region of the organic insulator, it is possible to provide a region with a high concentration of the antioxidants (A) and (B) in a thin range in the surface region of the organic insulator. In this case, the antioxidants (A) and (B) are concentrated in the surface region, so that the volume ratio of the internal region, which occupies most of the organic insulator, can be increased. When the volume ratio of the portion with a low content of the antioxidants (A) and (B) is increased, the decrease in the glass transition point (Tg) of the organic resin can be suppressed and the heat resistance can be increased. The thickness of the portion with a high content of the antioxidants (A) and (B) having a layered form is preferably 0.05 to 0.3 when the thickness of the organic insulator is 1, although it depends on the thickness of the organic insulator. In this case, it is preferable that the antioxidants (A) and (B) are uniformly dispersed in the surface and internal regions of the organic insulator. The portion with a large amount of the antioxidants (A) and (B) is preferably the entire surface of the organic insulator, but in some cases, it may be provided only in the portion where the characteristics need to be maintained.

[0023] The method of mixing each component including the nitrogen-based antioxidant (A) and the phenol-based antioxidant (B) when preparing the organic insulator is not particularly limited. Examples of the mixing method include a solution mixing method in which all components are uniformly dissolved or dispersed in a solvent, and a melt blending method in which the components are heated using an extruder or the like. An example of a suitable solvent used in the solution mixing method is xylene. In this case, the mass ratio of the solid content (resin) to the solvent is not particularly limited, and is, for example, about 60:40 to 20:80. In addition to xylene, other solvents such as aromatic solvents such as toluene, benzene, and ethylbenzene, hydrocarbon solvents such as normal hexane, cyclohexane, and methylcyclohexane, ketone solvents such as acetone, tetrahydrofuran, and chloroform may be used, and xylene may be used in combination with the other solvents mentioned above.

[0024] The organic resin may be, for example, a resin composition containing a cyclic olefin copolymer as a main component and a peroxide. The peroxide may have a benzene ring. The cyclic olefin copolymer may be thermosetting. By applying a material containing a thermosetting cyclic olefin copolymer as a main component to the organic resin, an organic insulator with a low relative dielectric constant and dielectric loss tangent in the high frequency range can be obtained. The dielectric properties are, for example, a relative dielectric constant of 2.7 or less and a dielectric loss tangent of 0.0045 or less at 125°C and 79 GHz.

[0025] The cyclic olefin copolymer is a polyolefin copolymer having a cyclic structure. Specifically, the cyclic olefin copolymer is a copolymer of a cyclic olefin and another monomer copolymerizable with the cyclic olefin. The ratio of the cyclic olefin to the other monomer is not particularly limited, and may be, for example, about 10 to 80% by mass of the cyclic olefin and about 20 to 90% by mass of the other monomer. Examples of the cyclic olefin include norbornene-based monomers, cyclic diene-based monomers, and vinyl alicyclic hydrocarbon-based monomers. Specifically, examples of the cyclic olefin include norbornene, vinylnorbornene, phenylnorbornene, dicyclopentadiene, tetracyclododecene, cyclopropene, cyclobutene, cyclopentene, cyclohexene, cyclohexadiene, and cyclooctadiene. These cyclic olefins may be used alone or in combination of two or more.

[0026] The thermosetting cyclic olefin copolymer preferably has a crosslinkable functional group in the molecule. Such a crosslinkable functional group may be a group that can undergo a crosslinking reaction by a radical derived from a peroxide having a benzene ring. Examples of such a functional group include at least one selected from the group consisting of a vinyl group, an allyl group, an acrylic group, and a methacrylic group.

[0027] The resin composition may further contain a monomer having at least two ethylenically unsaturated groups in the molecule. Such a monomer acts as a crosslinking agent between cyclic olefin copolymers. This monomer exists in the resin composition in a state of small molecular weight, so it is easy to enter between cyclic olefin copolymers. Furthermore, since it is an organic molecule having two or more ethylenically unsaturated groups, it has the property of easily reacting with crosslinkable sites of multiple adjacent cyclic olefin copolymers. This makes it possible to increase the glass transition temperature (Tg).

[0028] Examples of the monomer include tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, and triallyl isocyanurate. Among these, tricyclodecane dimethanol diacrylate is preferred. When tricyclodecane dimethanol diacrylate is contained in the resin composition, the glass transition point (Tg) becomes 150°C or higher, and the increase rate of the dielectric tangent after being left at high temperature can be reduced. In this case, the content ratio of the monomer is preferably 1 part by mass or more and 8 parts by mass or less when the cyclic olefin copolymer is 100 parts by mass.

[0029] When such a monomer is present in the resin composition, this monomer is present between the cyclic olefin copolymers, and a cured product can be obtained in which the cyclic olefin copolymers are strongly crosslinked by the two or more ethylenically unsaturated groups present. Specifically, a cured product (organic insulator) having a glass transition temperature (Tg) of 133°C or higher, preferably 136°C or higher after curing can be obtained. In addition, the electrical properties are such that the relative dielectric constant (Dk) at room temperature (25°C) and a frequency of 79 GHz is 2.7 or less, and the dielectric loss tangent under the same conditions is 0.002 or less. Furthermore, with regard to the dielectric loss tangent (Df), it is possible to obtain a cured product (organic insulator) with a small dielectric loss tangent even when left in an environment at a temperature (e.g., 125°C) higher than room temperature (25°C) for a long period of time (e.g., 2000 hours or more).

[0030] When the organic resin is formed from a cyclic olefin copolymer, it is preferable to use a thermosetting cyclic olefin copolymer (thermosetting COC) as the main component from the viewpoint of heat resistance.

[0031] According to the organic insulator of the present disclosure, the dielectric constant and dielectric loss tangent can be prevented from increasing even when exposed to high temperatures in the air. As a result, the dielectric properties are stable even in high-temperature environments, and therefore, devices using metal-clad substrates and wiring substrates provided with the organic insulator can be prevented from experiencing a decrease in performance even when used in high-temperature environments, and the reliability can be improved.

[0032] The organic insulator may contain a filler (inorganic particles). Furthermore, the organic insulator may contain a flame retardant. For example, if the dielectric properties (dielectric constant, dielectric loss tangent) of an organic insulator change significantly at either the measurement frequency or the measurement direction, the transmission properties of a wiring board using an organic insulator as an insulating layer are likely to change over time. Therefore, an organic insulator that has a low dielectric constant and dielectric loss tangent and is unlikely to change significantly at either the measurement frequency or the measurement direction is preferable.

[0033] To obtain such an organic insulator, it is preferable to use a cyclic olefin copolymer having a cross-linking site with low polarity and little anisotropy, and to use a filler and a flame retardant that are isotropic in shape. In this case, it is preferable that the shapes of both components have an aspect ratio close to 1. It is particularly preferable that the shapes of these fillers and flame retardants are spherical or close to spherical. Here, a shape close to spherical means that when the filler and flame retardant are observed, the outline of their shapes has curved parts. For example, the proportion of the curved parts in the outline is 80% or more.

[0034] As the filler material, silica, that is, spherical silica, is preferable. The flame retardant is preferably one containing a bromine component, i.e., a bromine-based flame retardant. Furthermore, it is preferable that the filler and the flame retardant are individually dispersed in the organic insulator via the organic resin. In particular, it is preferable that almost all of the flame retardant and the filler are observed as particles with the organic resin sandwiched between them. By observing almost all of the flame retardant and the filler as particles with the organic resin sandwiched between them, the anisotropy of the dielectric properties of the organic insulator can be reduced and the isotropy can be increased. In this way, an organic material can be obtained in which the frequency dependence of the dielectric constant / dielectric loss tangent is small and the difference in characteristics between the surface direction and the thickness direction is small.

[0035] This organic insulator is made of a cured resin that has a low polarity and contains rigid norbornene rings. The cured resin containing norbornene rings has a three-dimensional structure, which fixes the molecules to each other, minimizing molecular motion. The use of a bromine-based flame retardant and spherical silica also contributes to the improvement of the properties of this organic insulating material. In this case, it is better to use a non-polar flame retardant and isotropic spherical silica that does not show anisotropic properties. Furthermore, it is better for almost all of these flame retardants and silica to be dispersed through the organic resin. In this way, the anisotropy of the dielectric properties can be reduced in the organic insulator. When the organic insulator has a sheet shape, the difference in the dielectric properties between the planar direction and the thickness direction can be reduced.

[0036] The organic resin may contain a cured cyclic olefin copolymer having a structure of nitrogen and di-t-butylphenol. The state containing the cured cyclic olefin copolymer having a structure of nitrogen and di-t-butylphenol may be in the same molecule or may be a mixture of two types of molecules. The state containing the cured cyclic olefin copolymer having a structure of nitrogen and di-t-butylphenol can be detected by pyrolysis GC-MS. In the case of such organic insulators (organic resins), the nucleophilic nitrogen and electrophilic phenol moieties tend to interact with each other and come into close proximity, which makes it easier for the molecules in the organic resin to be fixed in a three-dimensional structure. As a result, the molecules present inside the organic resin are less likely to move even when the frequency of the applied power changes, and the resin exhibits a stable relative dielectric constant and dielectric loss tangent.

[0037] By using such an organic insulator, a wiring board can be obtained in which the change in dielectric properties is small even when the frequency changes or when the direction of the wiring formed inside or on the surface of the wiring board changes. In this case, the change in dielectric properties is small means that the change in dielectric properties is small even when the measurement frequency is different. In addition, the change in dielectric properties is small means that when the organic insulator is, for example, sheet-shaped, the change in dielectric properties is also small between the planar direction (in the XY plane) and the thickness direction (Z direction).

[0038] The metal-clad laminate of the present disclosure includes a metal foil laminated on at least one surface of an organic insulator. This allows the metal-clad laminate to have the dielectric properties exhibited by the organic insulator. Furthermore, the metal-clad laminate has the properties of the organic insulator, such as oxidation resistance, adhesion to the metal foil, and insulating properties.

[0039] The metal foil is not particularly limited, and examples thereof include copper foil such as electrolytic copper foil and rolled copper foil, aluminum foil, and composite foils obtained by laminating these metal foils. Among these metal foils, copper foil is preferred. The thickness of the metal foil is not particularly limited, and is preferably, for example, about 5 to 105 μm. In this case, the surface roughness Ra of the metal foil is preferably, for example, 0.5 μm or less, particularly 0.2 μm or less. In order to ensure the adhesive strength between the metal foil and the organic insulator, the surface roughness (Ra) is preferably 0.05 μm or more.

[0040] The metal-clad laminate is obtained by stacking a desired number of organic insulators and metal foils, and then hot-pressing and molding them. If the dielectric tangent of the metal-clad laminate 100 is, for example, 0.004 or less, sufficient electrical properties such as relative dielectric constant are exhibited, and the metal-clad laminate can be used, for example, as a wiring board for high frequency use.

[0041] The wiring board of the present disclosure includes a plurality of insulating layers and metal foils (conductor layers) disposed between the insulating layers, and the insulating layers are preferably made of the organic insulator. The wiring board also has the properties of the organic insulator, such as dielectric properties, oxidation resistance, adhesion to the metal foils, flame retardancy, and insulation properties.

[0042] The wiring board can be applied to a multilayer wiring board in which insulating layers and metal foils are alternately laminated, as well as a wiring board having a cavity structure. The wiring board can be obtained, for example, by stacking the inner layer board in which a circuit and a through hole are formed on the above-mentioned metal-clad laminate and a prepreg, laminating a metal foil on the surface of the prepreg, and then heating (curing) and pressing. Furthermore, a circuit and a through hole may be formed in the metal foil on the surface to form a multilayer printed wiring board.

[0043] The wiring board can be obtained, for example, through a process of preparing a resin composition that will be the above-mentioned organic insulator, a process of forming a semi-cured insulating sheet by molding the resin composition into a sheet, a process of coating the surface of this insulating sheet with a metal foil that will be a conductor layer, and a process of heating and pressing the insulating sheet coated with the metal foil under predetermined conditions (temperature, pressure, and atmosphere). The wiring board obtained in this way is suitable as a wiring board for high frequency use with excellent long-term reliability because the insulating layer is formed, for example, of the above-mentioned organic insulator.

[0044] The organic insulator of the present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples. EXAMPLES

[0045] The organic resin used was a thermosetting cyclic olefin copolymer having a crosslinkable functional group (manufactured by Mitsui Chemicals, Inc.). The peroxide having a benzene ring used was Perbutyl D (registered trademark, di-t-butyl peroxide, manufactured by Nippon Oil & Fats Co., Ltd.). The organic resin was made by adding 1.8 parts by mass of Perbutyl D (peroxide) to 100 parts by mass of cyclic olefin copolymer (COC).

[0046] As the nitrogen-based antioxidant (A), Chimassorb 2020 (hindered amine polymer, manufactured by BASF Japan) was used.

[0047] As the phenol-based antioxidant (B), Irganox 1010 (a di-t-butylphenol derivative manufactured by BASF Japan) was used.

[0048] Next, the nitrogen-based antioxidant (A) and the phenol-based antioxidant (B) were mixed with the cyclic olefin copolymer and Perbutyl D (peroxide) in the ratios shown in Table 1 per 100 parts by mass of the organic resin, and the mixture was stirred at room temperature (25°C) to prepare a resin composition (Sample No. 1-13).

[0049] Next, the obtained resin composition was dissolved in xylene to obtain a resin varnish. The mass ratio of the resin composition to xylene was 40:60. The obtained resin varnish was molded into a sheet using a bar coater and dried at 150°C for 4 minutes to obtain a sheet-like molded product having a thickness of 15 μm.

[0050] The obtained sheet-like molded product (hereinafter, sometimes referred to as a sheet) was cut into small pieces. Six of these small pieces were stacked together, and copper foils having a thickness of 18 μm were laminated on both sides of the stack to produce a laminate.

[0051] Next, the laminate was heated at 200° C. for 120 minutes under a pressure of 4 MPa to obtain a copper-clad laminate having a thickness of about 120 μm.

[0052] The copper foil was peeled off from the obtained copper-clad laminate to take out the organic insulator, and the dielectric constant Dk and dielectric loss tangent Df at 79 GHz were measured using the balanced disk resonator method. The dielectric constant Dk and dielectric loss tangent Df were measured for the initial sample (room temperature of 25°C) and the sample after being left at 125°C for 2000 hours. The results are shown in Tables 1 and 2.

[0053] In addition, the obtained organic insulator was subjected to dynamic mechanical analysis (DMA) to measure the behavior of the loss tangent, and the peak temperature of the loss tangent was determined as the glass transition point (Tg). The results are shown in Table 1.

[0054] The adhesive strength of the copper foil was measured using the prepared copper-clad laminate. The peel strength of the copper foil was measured using an autograph by pulling the copper foil in a direction perpendicular to the surface of the organic insulator. Five samples were measured, and the average value was calculated. The results are shown in Table 1. [Table 1] [Table 2] As is clear from the results in Table 1, the initial relative dielectric constant Dk at 79 GHz for sample No. 1-9 was 2.72 or less. All samples had two glass transition points (Tg), one below 100°C and one above 100°C, with the higher glass transition point (Tg) being 130°C or more. The peel strength was 0.5 kN / m.

[0055] As is clear from the results in Table 2, sample No. 1-9, in which the ratio (A / B) of the nitrogen-based antioxidant (A) to the phenol-based antioxidant (B) was 0.5 or more and 3.1 or less in mass ratio, had a relative dielectric constant Dk of 2.74 or less and a dielectric dissipation factor Df of 0.0045 or less at 79 GHz after being left at 125°C for 2000 hours.

[0056] In particular, when the ratio (A / B) of the two antioxidants (A) and (B) was 0.5 to 3.0 (sample No. 1-7), the dielectric tangent Df at 125° C. after 2000 hours was 0.0038 or less.

[0057] Furthermore, when the total amount of both antioxidants (A) and (B) was 0.9 to 2.1% (samples Nos. 1 to 5 and 7), the dielectric loss tangent Df at 125° C. after 2000 hours was 0.0037 or less. EXAMPLES

[0058] The organic resin used was a thermosetting cyclic olefin copolymer having a crosslinkable functional group (manufactured by Mitsui Chemicals, Inc.). Percumyl D (registered trademark, dicumyl peroxide, manufactured by Nippon Oil & Fats Co., Ltd.) was used as a peroxide having a benzene ring. The organic resin was made by adding 1.4 parts by mass of Percumyl D (peroxide) to 100 parts by mass of cyclic olefin copolymer (COC).

[0059] As the nitrogen-based antioxidant (A), Chimassorb 944 (hindered amine polymer, manufactured by BASF Japan) was used. As the phenol-based antioxidant (B), Irganox 1010 (a di-t-butylphenol derivative manufactured by BASF Japan) was used.

[0060] Next, the nitrogen-based antioxidant (A) and the phenol-based antioxidant (B) were blended in an amount of 0.6 parts by mass and 0.3 parts by mass, respectively, per 100 parts by mass of the organic resin into the composition obtained by adding Percumyl D (peroxide) to the above cyclic olefin copolymer.

[0061] In addition to the antioxidant, a filler and a flame retardant were also added. The filler was a silica filler (SFP-30M manufactured by Denka), and the flame retardant was a mixture of ethylene bis pentabromobenzene and pentabromophenyl ether in a mass ratio of 1:1. The amount of the filler and the flame retardant added was 50 parts by mass for every 100 parts by mass of the cyclic olefin copolymer.

[0062] These were mixed at room temperature (25°C) using a ball mill to obtain a resin varnish (Sample No. 14-26). This resin varnish was formed into a sheet using a bar coater and dried at 150°C for 4 minutes to obtain a sheet having a thickness of 40 μm.

[0063] The resins used in Samples No. 19-21 are as follows: Liquid crystal polymer: RF-705 (Panasonic) Fluororesin: Polytetrafluoroethylene (PTFE) (Rogers RO3003) Polyphenylene ether: R5410 (Panasonic)

[0064] The resulting sheet was cut into small pieces, 10 of which were stacked together, and the stack was heated at 200° C. for 120 minutes under a pressure of 4 MPa to obtain a cured resin having a thickness of approximately 120 μm.

[0065] The relationship between the measurement frequency and the dielectric constant and dielectric loss tangent of the obtained cured resin was investigated. The results are shown in Table 3. In Table 3, the dielectric constant and dielectric loss tangent were measured using a coaxial excitation balanced disk resonator method. The measurement direction was the Z direction. In other words, the dielectric constant and dielectric loss tangent were calculated from the resonance characteristics excited inside a balanced disk resonator that was electric field-coupled from the center of the disk by a coaxial excitation line. Two 5 cm square samples were used. From the measurement results, the rate of variation of the dielectric constant and dielectric loss tangent at 15 GHz and 79 GHz was obtained, and a rate of variation of the dielectric constant within 0.5% and a rate of variation of the dielectric loss tangent within 10% were deemed good. The rate of change was calculated using the following formula and expressed as an absolute value. Fluctuation rate = [(79 GHz value - 15 GHz value) / 15 GHz] x 100

[0066] Nitrogen and phenol were detected by pyrolysis GC-MS under the following detection conditions: <Detection conditions> Heating conditions: 600℃ (in helium flow) Pyrolysis equipment: FRONTIER LAB DOUBLESHOT PYROLIZER PY2020iD GC-MS (gas chromatograph mass spectrometer): Shimadzu QP2010Plus

[0067] The shape of the filler was observed under a microscope. The dispersion state of the filler was evaluated by observing the cross section of the sample with a scanning electron microscope and identifying whether or not a plurality of filler particles were aggregated in the sample. Specifically, the particle size of each filler (silica) present in the sample was first obtained from the photograph. At this time, the state in which aggregates existed was defined as a state in which multiple fillers were gathered together and in contact with each other. The aggregates extracted were those with a diameter 10 times or more the average particle size of the filler. The presence of aggregates means that multiple fillers come into contact with each other and the observed area contains at least one aggregate with a diameter 10 times or more the average particle size of the filler. The shape of the filler is said to be spherical when there are no straight lines in the outline of the observed filler and the entire circumference is curved, and the aspect ratio satisfies the condition of 1.3 or less.

[0068] The aspect ratio is the ratio of the length in the direction showing the longest length (diameter) of the filler to the length in the direction perpendicular to the direction showing the longest length (diameter). The length in the direction perpendicular to the direction showing the longest length (diameter) is called the shortest diameter. The aspect ratio is the relationship of longest diameter L1 / shortest diameter L2. A polygon is one in which there are two or more straight lines in the outline of the filler observed. [Table 3]

[0069] From Table 3, it can be seen that samples Nos. 14 to 18 have smaller variations in dielectric tangent with frequency than samples Nos. 19 to 26.

[0070] Furthermore, the relationship between the measurement direction and the dielectric constant and dielectric loss tangent of the cured resin obtained above was investigated. The results are shown in Table 4. In Table 4, all measurements were taken at a wavelength of 79 GHz. Measurements were taken in the XY directions using the hollow cylindrical resonator method, and in the Z direction using the coaxially excited balanced disk resonator method described above. In the hollow cylindrical resonator method, a dielectric substrate (sample) is sandwiched between a cylindrical cavity resonator divided in the center. The dielectric constant and dielectric loss tangent are calculated from the resonance characteristics of the resonator. The sample is a single 5 cm square piece. The variation rate of the dielectric constant in the XY direction and the Z direction was within 1%, and the variation rate of the dielectric tangent was within 10%, which was considered to be good. The variation rate was calculated using the formula above. The other measurement methods were the same as those in Table 3. [Table 4]

[0071] From Table 4, it can be seen that, compared with samples Nos. 19-26, the variation in dielectric tangent due to the measurement direction is smaller for samples Nos. 14-18.

Claims

1. The present invention relates to a composition comprising an organic resin as a main component, the organic resin containing at least an antioxidant (A) containing a nitrogen atom and a phenol-based antioxidant (B), The organic insulator has a higher content of the nitrogen atom-containing antioxidant (A) and the phenol-based antioxidant (B) in a surface region than in an internal region.

2. 2. The organic insulator according to claim 1, wherein a ratio (A / B) of the nitrogen atom-containing antioxidant (A) to the phenol-based antioxidant (B) is 0.5 or more and 3.1 or less in mass ratio.

3. 3. The organic insulator according to claim 2, wherein a ratio (A / B) of the nitrogen atom-containing antioxidant (A) to the phenol-based antioxidant (B) is 0.5 or more and 3.0 or less in mass ratio.

4. 2. The organic insulator according to claim 1, wherein a total amount of the nitrogen-containing antioxidant (A) and the phenol-based antioxidant (B) is 0.9 parts by mass or more and 4.5 parts by mass or less per 100 parts by mass of the organic resin.

5. 5. The organic insulator according to claim 4, wherein a total amount of the nitrogen atom-containing antioxidant (A) and the phenol-based antioxidant (B) is 0.9 parts by mass or more and 2.1 parts by mass or less per 100 parts by mass of the organic resin.

6. 2. The organic insulator according to claim 1, wherein the nitrogen atom-containing antioxidant (A) is a hindered amine-based compound, and the phenol-based antioxidant (B) is a di-t-butylphenol derivative.

7. The organic insulator of claim 1 , wherein the organic resin comprises a thermosetting resin.

8. The organic insulator according to claim 7 , wherein the main component of the thermosetting resin is a cyclic olefin copolymer.

9. 10. The organic insulator of claim 1, further comprising a spherical silica filler and a brominated flame retardant.

10. An organic insulator according to any one of claims 1 to 9, and a metal foil laminated on at least one surface of the organic insulator.

11. A wiring board comprising: a plurality of insulating layers formed of the organic insulator according to any one of claims 1 to 9; and a metal foil disposed between the insulating layers.

12. A metal-clad laminate comprising an organic insulator having an organic resin as a main component, the organic resin containing at least an antioxidant (A) containing a nitrogen atom and a phenol-based antioxidant (B), and a metal foil laminated on at least one side of the organic insulator.

13. A wiring board comprising a plurality of insulating layers constituted by an organic insulator containing, as a main component, an organic resin and at least an antioxidant (A) containing a nitrogen atom and a phenol-based antioxidant (B) in the organic resin, and a metal foil disposed between the insulating layers.

Citation Information

Patent Citations

  • Cyclic olefin copolymer and crosslinked body thereof

    JP2010100843A

  • Insulating material and laminated structure

    JP2013071960A

  • Conductive laminate, foam or crack reduction sheet, and foam or crack reducing method

    JP2016074220A

  • Resin composition and covered electric wire using the same

    JP2020015812A

  • Peroxide-containing polyolefin compounds

    JP2020532604A